Long-lasting impact of perinatal dietary supplementation of omega 3 fatty acids on mevalonate pathway: potential role on neuron trophism in male offspring hippocampal formation. (2nd January 2022) - Tonini, Claudia; Schiavi, Sara; Macca, Fabrizio; Segatto, Marco; Trezza, Viviana; Pallottini, Valentina
ABSTRACT: Objective: We were aimed at evaluating the long-term impact of perinatal an omega-3 fatty acid-enriched diet on the mevalonate/cholesterol pathway in the brain of male offspring. Methods: Female rats were fed with standard or omega-3 fatty acid-enriched diet during pregnancy and lactation. Liver, brain and plasma were collected from infant, adolescent and adult male offspring for subsequent biochemical and morphological analyses. Results: The omega-3 enriched diet induced region-dependent changes of the 3-hydroxy 3-methylglutaryl Coenzyme A reductase in the brain and affected notably RhoA/CREB signaling and the nerve growth factor content in the hippocampus. Our data reveal a long-lasting impact of perinatal omega-3 fatty acid supplementation on hippocampal nerve growth factor levels mediated by reduced 3-hydroxy 3-methylglutaryl Coenzyme A reductase activation state and enhanced CREB signaling. Discussion: These data underline the importance of the perinatal omega-3 enriched diet for adult brain function and reveal a new pathway important for nerve growth factor regulation.